2006
DOI: 10.1029/2006gl027736
|View full text |Cite
|
Sign up to set email alerts
|

Formation of dayside low‐latitude boundary layer under northward interplanetary magnetic field

Abstract: A three‐dimensional (3‐D) global hybrid simulation is carried out to study the formation of the dayside low‐latitude boundary layer (LLBL) under a purely northward interplanetary magnetic field (IMF). Magnetic reconnection in both northern and southern hemispheres leads to a continued formation of newly closed field lines on the dayside, and a subsequent formation of the LLBL by capture of the magnetosheath ions on the original magnetosheath field lines, as the newly closed field lines shorten. The formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…In a recent study (Lin and Wang, 2006) showed that under a purely northward interplanetary magnetic field (IMF), magnetic reconnection in both northward and Southern Hemispheres leads to a continued formation of newly closed field lines on the dayside, a feature that we observe in our simulation (see Fig. 4a and 5).…”
Section: Impact Of Solar Wind Depression On Large Scale Structures: Tsupporting
confidence: 71%
See 1 more Smart Citation
“…In a recent study (Lin and Wang, 2006) showed that under a purely northward interplanetary magnetic field (IMF), magnetic reconnection in both northward and Southern Hemispheres leads to a continued formation of newly closed field lines on the dayside, a feature that we observe in our simulation (see Fig. 4a and 5).…”
Section: Impact Of Solar Wind Depression On Large Scale Structures: Tsupporting
confidence: 71%
“…Note that new particles injected from the solar wind on lateral surfaces have a half-space Maxwellian distribution velocity. The boundary conditions for the fields assume no reflection on the box edges as proposed by Lindman (1975). Charge conservation is fulfilled using charge and current deposition scheme as proposed by Villasenor and Buneman (1992).…”
Section: Code Description: Initial Conditionsmentioning
confidence: 99%
“…It has been demonstrated that hybrid simulation is a powerful tool to solve physical problems in a system dominated by ion dynamics at a timescale ω ∼ Ω i and spatial scale kρ i ∼ 1, where ω is the wave frequency, k is the wave number, and Ω i and ρ i are the ion gyrofrequency and Larmor radius, respectively. Our 3‐D global‐scale hybrid code [ Lin and Wang , 2005, 2006] has been developed following the hybrid scheme of Swift [1996], and has been used to investigate ion dynamics and electromagnetic waves excited at the bow shock and cusp self‐consistently. In our model, protons are treated as fully kinetic particles and electrons are treated as a massless fluid, assuming quasi‐charge neutrality.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The inner boundary layer is composed of newly closed field lines that are formed from magnetosheath field lines by double magnetic reconnection, first poleward of one cusp and later poleward of the other cusp. In a 3‐D hybrid simulation, Lin and Wang [2006] showed that as a result of the double high‐latitude reconnection process, a thick magnetopause boundary layer is formed by the magnetosheath ions captured on the newly closed field lines and the transmitted magnetosheath ions near the high‐latitude X lines.…”
Section: Introductionmentioning
confidence: 99%